(3GNJUGQ GdahGFO GddWjaI hGdefGaY GdTQjaIs - (3CHh GdYHGS,J (B1200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj gh Cgd hGdceGd hGdaVd GdYXje GdOGFe s
(3BNQgG (B:s
(3hbO CTQfG Edi gPG GdeYfi aj Chd GdcJGH JCedg hGddg Gdehab ddUhGH GfJgi HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B351s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B- (3GdeZQH (B(1370 (3O(B) s
Keywords: (3GdMQha h GdChaGbs